1969
DOI: 10.1177/002188636900500204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feedback on Interpersonal Sensitivity in Laboratory Training Groups

Abstract: The 69 participants in the 1966 Rocky Mountain Workshop in Group Development, sponsored by the Adult Education Council of Metropolitan Denver, served as subjects in the present investigation. The study was designed to determine whether an instrumented feedback procedure based on sociometric ratings would help the members of laboratory training groups increase their sensitivity to others. It was found that subjects in experimental groups who filled out sociometric questionnaires and received feedback on their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The exchange of feedback among group members is widely considered to be an essential element in promoting interpersonal learning within the therapeutic group setting. Members benefit by learning more about themselves from the feedback they receive and by the sense of contribution and the increased interpersonal sensitivity that is realized as a result of giving feedback to others (Myers, Myers, Goldberg & Welch, 1969; Kaul & Bednar, 1978).…”
mentioning
confidence: 99%
“…The exchange of feedback among group members is widely considered to be an essential element in promoting interpersonal learning within the therapeutic group setting. Members benefit by learning more about themselves from the feedback they receive and by the sense of contribution and the increased interpersonal sensitivity that is realized as a result of giving feedback to others (Myers, Myers, Goldberg & Welch, 1969; Kaul & Bednar, 1978).…”
mentioning
confidence: 99%
“…There is, in fact, considerable support for viewing feedback as one of the most important dimensions of the therapeutic group process (Bednar & Kaul, 1978; Bennis, 1964; Campbell & Dunnette, 1968; Jacobs, 1974). Results of several studies have demonstrated that feedback over and above that normally occurring is related to more successful group and individual outcomes (Flowers & Booraem, 1976; Jenkins, 1948; Kolb, Winter, & Berlew, 1968; Myers, Myers, Goldberg, & Welch, 1969; Stock, 1964).…”
mentioning
confidence: 99%
“…Butler & Ese, 1983; Davies & Jacobs, 1985; Fisher & Ellis, 1990; Haslett & Oglivie, 1988; M. Jacobs, Jacobs, Feldman, & Cavior, 1973; Kivlighan, 1985; Myers, Myers, Goldberg, & Welch, 1969).…”
Section: Discussionmentioning
confidence: 99%